Odobenus rosmarus Linnaeus 1758 - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
Walrus Odobenus rosmarus French: Morse / German: \Walross / Spanish: Morsa Other common names: Atlantic Walrus (rosmarus); Laptev Walrus (Laptev Sea population); Pacific Walrus (divergens) Taxonomy. Phoca rosmarus Linnaeus, 1758, “intra Zonam arcticam Europe, Asie, America.” The “Laptev Walrus” (laptevi) described by K. K. Chapskii in 1940 in the Laptev Sea is not recognized here as distinct subspecies. Mitochondrial sequence data presented by C. Lindqvist and her colleagues in 2009 suggested that the population in the Laptev Sea was the westernmost population of the “Pacific Walrus” (dwvergens) and not a distinct subspecies. Twosubspecies recognized. Subspecies and Distribution. O.r.rosmarusLinnaeus,1758—NCanada(HudsonBay)toWGreenlandanddiscon-tinuouslyfromEGreenlandtoSvalbardandNRussia(FranzJosefLandandKaraSea);occasionallyreportedinIcelandandstragglersinWEuropeStotheBayofBiscay. O. r. divergens Illiger, 1815 — Laptev Sea off N Russia, Bering and Chukchi seas in N Russia and Alaska; vagrant individuals reported S to New England, USA. Descriptive notes. Total length 250-350 cm, averaging 315 cm (males) and ¢.260 cm (females); weight 800-1800 kg, averaging 1500 kg (males) and c.1000 kg (females). Newborns are ¢.10 cm in total length and weigh ¢.85 kg. Walruses have relatively small heads, broadly flattened muzzles with thick short bristly whiskers, and robust torsos. Adult male and female Walruses are recognizable by their long external tusks (modified upper canine teeth). These canine teeth start developing early in life and can grow to 100 cm long and weight 5 kg. Tusks function as weapons, particularly for males during the breeding season; both sexes use them for support when foraging on the seafloor and as picks to anchor themselves to edges ofice floes and assist in pulling themselves out of the water. Post-canine teeth are very small pegs and appear to be largely non-functional. Chest and neck of adult males are massive and covered with wart-like nodules and tubercles. Skin is very thick, up to 6 cm on the ...